2018
DOI: 10.1139/cjss-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Identifying environmental phosphorus risk classes at the scale of Prince Edward Island, Canada

Abstract: The System for Automated Geoscientific Analyses (SAGA) is an open-source Geographic Information System (GIS), mainly licensed under the GNU General Public License. Since its first release in 2004, SAGA has rapidly developed from a specialized tool for digital terrain analysis to a comprehensive and globally established GIS platform for scientific analysis and modeling. SAGA is coded in C++ in an object oriented design and runs under several operating systems including Windows and Linux. Key functional features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 99 publications
(53 reference statements)
4
29
1
Order By: Relevance
“…Our results show that the Mehlich-3 method, which is widely used in acidic to near-neutral soils in North America including Canada, can be used on the soils of coastal BC. Use of the Mehlich-3 method offers the opportunity to assess other cations such as Al and Fe and therefore make it possible to adapt a PSI for BC soils (Khiari et al, 2000;Sims et al, 2002;Benjannet et al, 2018). We showed that P M3 , DPS and PSI were all closely related to silage corn DMY and P uptake across 11 soils with a wide range of soil test P levels.…”
Section: Agronomic and Environmental Implications For Soils With Highmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results show that the Mehlich-3 method, which is widely used in acidic to near-neutral soils in North America including Canada, can be used on the soils of coastal BC. Use of the Mehlich-3 method offers the opportunity to assess other cations such as Al and Fe and therefore make it possible to adapt a PSI for BC soils (Khiari et al, 2000;Sims et al, 2002;Benjannet et al, 2018). We showed that P M3 , DPS and PSI were all closely related to silage corn DMY and P uptake across 11 soils with a wide range of soil test P levels.…”
Section: Agronomic and Environmental Implications For Soils With Highmentioning
confidence: 79%
“…In Wallonia, Belgium, a study using 57 agricultural topsoil samples subject to diverse P management showed that DPS values between 20 and 30% corresponded to the agronomic optimum of soil P content (Renneson et al, 2015). In North America, the PSI has provided much-needed information to support environmental assessment at watershed, local, and provincial scales (Khiari et al, 2000;Sims et al, 2002;Benjannet et al, 2018).…”
Section: Relationship Between Silage Corn Yield and P Saturation Indimentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, including Canada, the oxalate soil extraction method used to assess DPS is not a routine analysis (Dayton et al 2014). Instead, the P saturation index (PSI) derived from Mehlich-3 P (P M3 ) and aluminum (Al M3 ) and (or) iron (Fe M3 ) is used as a proxy of DPS to assess the risk for P leaching from agricultural soils (Sims et al 2002;Pellerin et al 2006;Wang et al 2012;Benjannet et al 2018). Advantages of the Mehlich-3 extraction method include the capability to make fertilizer recommendations for P as well as other macroand micronutrients such as calcium, magnesium, and zinc to achieve optimum yields (Penn et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is limited information on how PSI is related to DPS or water-extractable P (Pw), two main indicators of the risk of P to the environment, across agricultural soils and cropping systems in south coastal BC. The PSI is influenced by soil pH (Benjannet et al 2018) and soil texture (Pellerin et al 2006). Penn et al (2018) showed that the P extracted by the Mehlich-3 method decreases with increasing soil pH because of changing P forms, partial neutralization of extractant pH, and consumption of extractant fluoride.…”
Section: Introductionmentioning
confidence: 99%